Behaviour of PVA fiber and SCM-modified UHPECC: a micromechanics approach - Priyanka, K.; Suganya, O. M. (Frontiers in Built Environment, 2025)
Ultra-high-performance engineered cementitious composites (UHPECC) are becoming increasingly important in modern construction. In this study, the Modified Andreasen and Andersen (MAA) particle packing model was employed to optimize the material proportions required for achieving superior strength and ductility. The effectiveness of the MAA model in achieving a dense matrix was validated through CT scan analysis. Additionally, micromechanics theory was applied to confirm the material design. All UHPECC mixes were evaluated for their crack patterns and strain-hardening behavior. Experimental results demonstrated that a quaternary blend of Supplementary Cementitious Materials (SCMs) significantly improved compressive strength and ultrasonic pulse velocity by up to 48% and 22%, respectively, compared to conventional UHPECC. The addition of 2% PVA fibre increased the strength and energy index by as much as 11% and 60%, respectively. These results help validate the fiber/matrix bonding behavior of UHPECC, which involves incorporating various types of SCM and fibers. The strong correlation between theoretical predictions and experimental outcomes further confirms the reliability of the design approach. Additionally, the microstructure of UHPECC was analyzed using X-ray Diffraction (XRD), Field-Emission Scanning Electron Microscopy (FE-SEM), and Thermogravimetric Analysis (TG).